2007
DOI: 10.1088/0964-1726/16/1/024
|View full text |Cite
|
Sign up to set email alerts
|

Vibration suppression of laminated composite beams using actuators of giant magnetostrictive materials

Abstract: This paper presents a simulation of vibration suppression of a laminated composite beam embedded with actuators of a giant magnetostrictive material subjected to control magnetic fields. It has been found that the strains generated in the material are not only significantly larger than ones created by many other smart materials but also exhibit some inherent nonlinearities. To utilize the full potential of these materials in active vibration control, these nonlinearities should be characterized in the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Murtyet al [62] created a laminated composite beam that contains a Terfenol-D particle embedded layer. Zhou and Zhou [63] later implemented a negative velocity feedback controller together with an analytical nonlinear constitutive model to mitigate the composite beam vibrations. Due to the large actuation force enabled by the Terfenol-D composite layer, this numerical study demonstrated a maximum effective damping factor of about 0.09.…”
Section: Active Vibration Controlmentioning
confidence: 99%
“…Murtyet al [62] created a laminated composite beam that contains a Terfenol-D particle embedded layer. Zhou and Zhou [63] later implemented a negative velocity feedback controller together with an analytical nonlinear constitutive model to mitigate the composite beam vibrations. Due to the large actuation force enabled by the Terfenol-D composite layer, this numerical study demonstrated a maximum effective damping factor of about 0.09.…”
Section: Active Vibration Controlmentioning
confidence: 99%
“…In this study, the magnetostrictive layers were used for the vibration suppression of the functionally graded shells. Recently, Zhou [2007] presented a simulation of vibration suppression of a laminated composite beam embedded with actuators of a giant magnetostrictive material subjected to control magnetic fields. In this study, the nonlinearities effect of giant magnetostrictive materials on vibration suppression has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Kannan and Dasgupta [11] formulated a 2D magnetostatic model with bi-directionally coupled magnetomechanical relations, current induced magnetic fields and electromagnetic body forces. Zhou et al [12] developed a 2D dynamic finite element model of a unimorph actuator with one way magnetomechanical coupling. The one-way coupled 3D model of Kim and Jung [13] describes force due to magnetostriction driving a coupled fluid-structural model for a sonar transducer.…”
Section: Introductionmentioning
confidence: 99%